2013
DOI: 10.1007/s00296-013-2905-y
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of people with osteoarthritis towards their conservative management: a systematic review and meta-ethnography

Abstract: This paper determines the perceptions of people diagnosed with osteoarthritis towards their conservative management strategies. A systematic review of the published (AMED, CINAHL, EMBASE, PsychINFO, SportsDisc, MEDLINE, Cochrane Clinical Trials Registry, PubMed) and unpublished/trial registry databases (WHO International Clinical Trials Registry Platform, Current Controlled Trials, the United States National Institute of Health Trials Registry, NIHR Clinical Research Portfolio Database) searched from their inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 44 publications
5
55
0
Order By: Relevance
“…The highest ranked FAQ by both patients and health care professionals, “What can I do myself to decrease symptoms and to prevent the OA from getting worse?” highlights the importance of patients’ need for information about OA and to feel confident in managing their condition . This need is in concordance with the guideline recommendation that self‐management is important for patients with hip or knee OA .…”
Section: Discussionsupporting
confidence: 67%
“…The highest ranked FAQ by both patients and health care professionals, “What can I do myself to decrease symptoms and to prevent the OA from getting worse?” highlights the importance of patients’ need for information about OA and to feel confident in managing their condition . This need is in concordance with the guideline recommendation that self‐management is important for patients with hip or knee OA .…”
Section: Discussionsupporting
confidence: 67%
“…Shared decision‐making models emphasize the importance of taking patients’ values and preferences into account. A recent meta‐synthesis indicated that patients with OA have mainly negative beliefs about the efficacy of conservative treatment options and prefer surgical treatment options . More in‐depth knowledge of patients’ reasons for choosing a specific OA treatment modality will aid shared decision making and might increase patients’ usage of conservative treatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Such a recommendation has been seen within the medication adherence literature in hypertension [22], asthma [23] and depression [24]. However, this understanding is particularly valid in the osteoarthritis population given the acknowledged variability in health beliefs regarding the condition itself, irrespective of beliefs surrounding pharmacological management [25]. Future interventions therefore should consider the individualisation of behaviour change, adopting models such as the social ecological model, to provide a theoretical underpinning for long-term behaviour change promoting medicine adherence.…”
Section: Discussionmentioning
confidence: 93%
“…There is an understanding that osteoarthritis may be 'just ageing' rather than 'medicalising' the condition [25]. The realisation that osteoarthritis is not currently curative, and that medications for symptom management are long-term, can have a negative impact, particularly on the fear of additional and longer-term usage.…”
Section: Discussionmentioning
confidence: 99%